2020
DOI: 10.2147/jmdh.s284786
|View full text |Cite
|
Sign up to set email alerts
|

<p>Educational e-Learning Tool to Improve Fascia Iliac Block Uptake for Neck of Femur Fracture Patients: A Multi-Disciplinary Approach</p>

Abstract: Background There are 75,000 neck of femur (NOF) fractures that occur each year in England and Wales. Prompt, adequate analgesia is a major priority in hip fracture management to reduce the risk of delirium and facilitate earlier return to mobility and independence. NICE guidelines recommend the use of fascia iliaca block (FIB) for NOF fracture patients. Current literature suggests that FIB significantly improves pre-operative pain scores; however despite this, the uptake of FIB still varies betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Alternatively, multiple studies have shown that an FICB can be taught to a variety of learners, including nurses, residents, emergency medicine physicians, and orthopaedists. 14,[16][17][18][19] Monzon et al demonstrated that emergency medicine residents could learn how to perform an FICB successfully with less than 5 minutes of instruction. 6 In addition, techniques that do not require ultrasound have been shown to be similar in their ability to provide pain control.…”
Section: Administering Physician Availabilitymentioning
confidence: 99%
“…Alternatively, multiple studies have shown that an FICB can be taught to a variety of learners, including nurses, residents, emergency medicine physicians, and orthopaedists. 14,[16][17][18][19] Monzon et al demonstrated that emergency medicine residents could learn how to perform an FICB successfully with less than 5 minutes of instruction. 6 In addition, techniques that do not require ultrasound have been shown to be similar in their ability to provide pain control.…”
Section: Administering Physician Availabilitymentioning
confidence: 99%